1973
DOI: 10.1085/jgp.61.4.509
|View full text |Cite
|
Sign up to set email alerts
|

The Reponse of Duck Erythrocytes to Norepinephrine and an Elevated Extracellular Potassium

Abstract: This paper presents evidence that duck erythrocytes regulate their size in isotonic media by utilizing a previously reported "volume-controlling mechanism." Two different experimental situations are examined. In the first, cells enlarge in a solution containing norepinephrine and an elevated [K]o; and in the second, enlarged cells shrink to their original size if the norepinephrine and excess potassium are removed. As the erythrocytes enlarge, K, Cl, and H2O accumulate. Shrinkage, in contrast, is accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…K moves toward its electrochemical equilibrium. ' Thus, the mechanism responsible for the K loss and volume regulation seen here resembles that reported previously (1,3). This is illustrated further by the observation that introducing ouabain (10-4 M) to the bathing medium has little effect on the changes in cell size (Fig.…”
Section: High-k Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…K moves toward its electrochemical equilibrium. ' Thus, the mechanism responsible for the K loss and volume regulation seen here resembles that reported previously (1,3). This is illustrated further by the observation that introducing ouabain (10-4 M) to the bathing medium has little effect on the changes in cell size (Fig.…”
Section: High-k Cellssupporting
confidence: 88%
“…The findings presented in this paper and elsewhere (1,3) show that under unsteady-state conditions a membrane pathway, C, becomes apparent in duck erythrocytes. It is through this pathway that the volume controlling mechanism, designated D, controls K loss from enlarged cells.…”
Section: Discussionsupporting
confidence: 70%
“…Previous reports in avian red cells indicated that catecholamines stimulate a cAMPdependent transport mechanism similar to that of the avian VRI response (Riddick et al, 1971 ;Kregenow, 1973;Kregenow et al, 1976). The possibility that hypertonicity and catecholamine-stimulated salt transport in avian and amphibian red cells may have common characteristics was anticipated by the work of Orskov (1954Orskov ( , 1956a.…”
Section: Discussionmentioning
confidence: 93%
“…B) NKCC1 AS A MECHANISM OF RVI. Coupled anion-cation transport in RVI was first demonstrated in avian RBCs (475,476) and shortly after in mammalian cells (32, 355). Similar to NHE1, NKCC1 is a major mediator of RVI in a wide variety of cell types studied.…”
Section: Slc12a2/nkcc1mentioning
confidence: 99%